2013
DOI: 10.24266/0738-2898.31.4.246
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and Polyploid Induction of Acer platanoides ‘Crimson Sentry

Abstract: Protocols were developed for micropropagation and induction of autopolyploids in a fastigiate cultivar of Norway maple (A. platanoides L. ‘Crimson Sentry’). Murashige and Skoog (MS) medium, woody plant medium (WPM), and Quoirin and Lepoivre medium were supplemented with 2 μM 6-benzylaminopurine (BA), meta-Topolin, 6-(γ,γ-dimethylallylamino) purine, kinetin, or thidiazuron to evaluate microshoot proliferation. Murashige and Skoog medium with 2 μM BA yielded the most microshoots (3.2) and longest microshoots (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…For example, Hussey and Hypher (1978) documented cytochimeral sugar beets after treatment with colchicine and observed that polyploid cells disappeared over subsequent subcultures. Similarly, Lattier et al (2013) found that for Acer platanoides, mixoploid tissues reverted to diploids over a 6-month period.…”
Section: Key Variables Influencing In Vitro Polyploid Induction Tissue Typementioning
confidence: 80%
See 4 more Smart Citations
“…For example, Hussey and Hypher (1978) documented cytochimeral sugar beets after treatment with colchicine and observed that polyploid cells disappeared over subsequent subcultures. Similarly, Lattier et al (2013) found that for Acer platanoides, mixoploid tissues reverted to diploids over a 6-month period.…”
Section: Key Variables Influencing In Vitro Polyploid Induction Tissue Typementioning
confidence: 80%
“…If all the initial cells are not affected, mixoploids or cytochimeras may form. Mixoploids have been widely observed in in vitro chromosome doubling of a wide range of species, including; Acer platanoides (Lattier et al, 2013), Helleborus sp. (Dhooghe et al, 2009b), Hypericum sp.…”
Section: Key Variables Influencing In Vitro Polyploid Induction Tissue Typementioning
confidence: 99%
See 3 more Smart Citations